Peran Dispensasi Kawin dalam Peningkatan Angka Pernikahan Dini di Wilayah Kotamadya Jakarta Barat - Rahmawati, Melinda; Nuraeni, Heni Ani (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
The purpose of this research is to know role of dispensation of marriage in the rise early married in West Jakarta. One of selection problem in Indonesian civilization as generally until now unfinished is early married. In national regulation, there are exclusion of wedding registration or â€œdispensation of marriageâ€ for candidate mate that by the law not eligible to married. Dispensation of marriage now made reason to registration of the wedding for candidate mate mentioned. Research methods are qualitative-explanative method which is source from reference about increase in population rate and marriage regulation. Generative approach who gave identification in detail about role of Dispensasi kawin in improvement early married in West Jakarta. The result of research is known dispensation of marriage currently as opportunity in the rise early married rates in West Jakarta. The conclusion of this research is dispensation of marriage the truth used to last option urgent for the sake of mutual benefit, now as opportunity to give legality on early married.